Forces and motion investigations - Kenney, Karen Latchana (Minneapolis : Lerner Publications, 2018)
Using real-world examples, facts, and a hands-on project raders will learn all about force and motion.
Introduction. Ultimate bounce -- Where does movement come from? -- How keeps the moon from floating into space? -- What makes things move? -- How does a rocket escape gravity?
Includes bibliographical references (page 31) and index.
5.0
3-6
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Gravity -- Juvenile literature; Gravity